Best practices for documentation of psychotropic drug-drug interactions in an adult psychiatric clinic - Kathryn Collins, PharmD, MSPH; Julie A. Dopheide, PharmD, BCPP, FASHP; Mengxi Wang, MPH; Talene Keshishian, MD (American Association of Psychiatric Pharmacists, 2023)
Introduction: Psychotropic drug-drug interactions (DDIs) contribute to adverse drug events, but many go undetected or unmanaged. Thorough documentation of potential DDIs can improve patient safety. The primary objective of this study is to determine the quality of and factors associated with documentation of DDIs in an adult psychiatric clinic run by postgraduate year 3 psychiatry residents (PGY3s). Methods: A list of high-alert psychotropic medications was identified by consulting primary literature on DDIs and clinic records. Charts of patients prescribed these medications by PGY3 residents from July 2021 to March 2022 were reviewed to detect potential DDIs and assess documentation. Chart documentation of DDIs was noted as none, partial, or complete. Results: Chart review identified 146 DDIs among 129 patients. Among the 146 DDIs, 65% were not documented, 24% were partially documented, and 11% had complete documentation. The percentage of pharmacodynamic interactions documented was 68.6% with 35.3% of pharmacokinetic interactions documented. Factors associated with partial or complete documentation included diagnosis of psychotic disorder (p = .003), treatment with clozapine (p = .02), treatment with benzodiazepine-receptor agonist (p<.01), and assumption of care during July (p = .04). Factors associated with no documentation include diagnosis of "other (primarily impulse control disorder)" (p<.01) and taking an enzyme-inhibiting antidepressant (p<.01). Discussion: Investigators propose best practices for psychotropic DDI documentation: (1) description and potential outcome of DDI, (2) monitoring and management, (3) Patient education on DDI, and (4) patient response to DDI education. Strategies to improve DDI documentation quality include targeted provider education, incentives, and electronic medical record "DDI smart phrases."